Construction of Hierarchical Copper‐Based Metal–Organic Framework Nanoarrays as Functional Structured Catalysts. Issue 10 (24th April 2017) - Zhang, Tianyu; Liu, Wenxian; Meng, Ge; Yang, Qiu; Sun, Xiaoming; Liu, Junfeng
Abstract: The immobilization of metal–organic framework (MOF) materials in a three‐dimensional (3 D) and oriented arrangement is critical for their application in heterogeneous catalysis. In this work, a coordination replication strategy was developed to construct Cu‐based MOFs into 3 D hierarchical nanoarray architectures by using Cu(OH)2 nanorod arrays as a sacrificial template. The Cu(OH)2 nanorod arrays served as the Cu source and coordinated with an organic ligand to form MOF crystals, and they also served as the 3 D substrate to support the growth of the Cu‐based MOFs. This strategy could also be applied to synthesize various hierarchical Cu‐based MOF arrays, which demonstrated the general efficacy of the method. Owing to their unique structural advantages (hierarchical porosity, large surface area, and intimate contact with the 3 D substrate), these MOF nanoarrays exhibit excellent catalytic activity and cycling stability in heterogeneous catalysis as structured catalysts. This strategy opens up new possibilities for the construction of immobilized MOF‐based 3 D nanoarrays for multipurpose applications. Abstract : A little bit of structure : A general coordination replication strategy is developed to fabricate hierarchical copper‐based metal–organic framework (MOF) arrays by using Cu(OH)2 nanorod arrays as a template and metal source. Owing to their unique structural advantages, the as‐prepared hierarchical MOF‐2 nanoarrays exhibit excellent catalytic activity and cycling stability in heterogeneous catalysis as a structured catalyst.